Neuropsychological outcome following frontal lobectomy for pharmacoresistant epilepsy in adults. (14th February 2017) - Busch, Robyn M.; Floden, Darlene P.; Ferguson, Lisa; Mahmoud, Shamseldeen; Mullane, Audrina; Jones, Stephen; Jehi, Lara; Bingaman, William; Najm, Imad M.
Abstract : Objective: This retrospective cohort study characterized cognitive and motor outcomes in a large sample of adults who underwent frontal lobe resections for treatment of pharmacoresistant epilepsy. Methods: Ninety patients who underwent unilateral frontal lobe resection for epilepsy (42 language-dominant hemisphere/48 nondominant hemisphere) between 1989 and 2014 completed comprehensive preoperative and postoperative neuropsychological evaluations that included measures of verbal and nonverbal intellectual functioning, attention/working memory, processing speed, language, executive functioning, verbal and visual memory, and motor functioning. Objective methods were used to assess meaningful change across a wide range of abilities and to identify factors associated with neuropsychological decline following frontal lobectomy. Detailed postoperative neuroimaging analysis was conducted to characterize region, extent, and volume of resection. Results: Forty-eight percent of patients did not demonstrate meaningful postoperative declines in cognition and an additional 42% demonstrated decline in 1 or 2 cognitive domains. When cognitive decline was observed, it usually occurred on measures of intelligence, visuomotor processing speed, or executive functioning. Side and site of resection were unrelated to cognitive outcome, but played a role in decline of contralateral manual dexterity following supplementary motor area resection. Higher preoperative ability, older age at surgery, absence of a malformation of cortical development on MRI, and poor seizure outcome were related to cognitive decline on some measures, but had poor sensitivity in identifying at-risk patients. Conclusions: The vast majority of patients who undergo frontal lobectomy for treatment of pharmacoresistant epilepsy demonstrate good cognitive and motor outcomes.